PENGEMBANGAN MODEL PEMBELAJARAN ELABORASI BERBANTUAN MULTIMEDIA PADA SISTEM PEREDARAN DARAH KELAS XI - Restu, Ratri Kanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The main background of this research is the learning of Biology for the 11th grader in SMA Bhayangkari 1 Kubu Raya who is still using the learning method that prioritize more of a storing information , remembering, and so on . However the information taught by the teacher is not fully effective and not fully recalled by the student because of the way of teaching used is pretty inconvenient. most teacher there taught the student by making them to memorize the materials, instead of letting them to apply it to their daily life and so on. The research was conducted with the approach of product development (research and development). This activity is focused on the development of media. Media were developed based development, namely (1) Designing products (2) Evaluation of product (3) The test product. The results of the research are students' learning outcomes using multimedia-assisted elaboration learning models for the concept of the human circulatory system at senior secondary schools have passed the minimum level of completeness defined for biology subjects at SMA Bhayangkari which is 75. Keywords: Elaboration Learning Model, Multimedia, Circulatory System.